DETERMINATION OF THE QUANTITY OF VITAMINS CONTAINED IN HYPERICUM PERFORATUM (Scientific journal of the Fergana State University, 2023)
Nowadays there is a growing interest and demand for natural medicines made from plants. Worldwide, the use of herbal medicines and nutritional supplements in the treatment of patients is the highest in European countries. Moreover, in Germany they have already realized that the use of plants in treatment has a more beneficial effect on the body than synthetic drugs. It is no secret that the large developed countries of Asia, Japan and China widely use plants in medicine. Therefore, in order to create a nutritional supplement from Hypericum perforatum, the vitamins contained in it were determined by liquid chromatography. During the experiment, vitamins B1, B2, B3, B6 and B9 were found in Hypericum perforatum. The identification of vitamin C among antioxidant vitamins indicates a positive effect of Hypericum perforatum on skin regeneration and prevention of aging processes.